New Advances in Second Language Acquisition Methodology in Higher Education - Blanka Klimova; Marcel Pikhart (MDPI AG, 2021)
This article summarizes new advances, as described by current research, in the methodology of teaching Business English as a lingua franca (BELF) in the era of mobile learning and provides the reader with hands-on strategies that are useful for BELF classes and applicable in distance learning. The primary objectives of this literature review are to explore the fundamental approaches which should help practitioners in their course preparation, development, and teaching. The paper provides the reader with the most up-to-date strategies for teaching BELF and brings ideas on how to utilize these principles in a mobile learning (m-learning) environment. The methods include a literature review of available articles exploring the research topic, i.e., BELF and its pedagogy, which was performed by finding relevant studies in the Web of Science and Scopus databases. The results indicate that there are three fundamental approaches recommended by the current research on the teaching of BELF, namely task-based activities/case studies, exploitation of authentic materials, and blended learning implementation. In summary, the paper provides the readers with an update on current approaches for teaching BELF in higher education when utilizing modern tools for foreign language learning, such as m-learning, blended learning, and hybrid learning.